Seven Principles for Selecting Software Packages. - DAMSGAARD, JAN; KARLSBJERG, JAN (Communications of the ACM, 2010)
The article presents a set of best practices and heuristics for purchasing commercial software packages. It provides a brief overview of the history of commercial software development, including the progression from customized programs made in-house to more standardized approaches which were outsourced. The ability of vendors to provide configurable packages due to open standards and generalized software is also discussed. The article focuses on seven principles which are said to be critically important in choosing between available software package options. These include the software vendor's network, the safety in numbers rule, and compatibility issues.